Obesity and the microbiome in atopic dermatitis: Therapeutic implications for PPAR-γ agonists - McAleer, Jeremy P. (Frontiers in Allergy, 2023)
Atopic dermatitis (AD) is an inflammatory skin disease characterized by epidermal barrier disruption, Th2 immune responses to skin allergens and microbial dysbiosis within affected lesions. Studies within the past decade have revealed genetic and environmental factors contributing to AD in children. Obesity is a metabolic disorder that often manifests early in life and is associated with reduced bacterial diversity, leading to skin colonization with lipophilic bacteria and intestinal colonization with pro-inflammatory species. These changes impair epithelial barriers and promote Th17 responses, which may worsen the severity of AD symptoms. While few studies have examined the contribution of microbiota in obesity-induced allergies, there is emerging evidence that PPAR-g may be an effective therapeutic target. This review discusses the microbiome in pediatric AD, treatment with probiotics, how disease is altered by obesity and therapeutic effects of PPAR-g agonists. While healthy skin contains diverse species adapted for specific niches, lesional skin is highly colonized with Staphylococcus aureus which perpetuates the inflammatory reaction. Treatments for AD should help to restore microbial diversity in the skin and intestine, as well as epithelial barrier function. Pre-clinical models have shown that PPAR-g agonists can suppress Th17 responses, IgE production and mast cell function, while improving the epidermal barrier and microbial homeostasis. Overall, PPAR-g agonists may be effective in a subset of patients with AD, and future studies should distinguish their metabolic and anti-inflammatory effects in order to inform the best therapies.